Addition to the summary of cryptogam vascular and gymnosperms plants: “Flora of the Lower Volga Region” (based on materials of the herbarium of SSU (SARAT)) - Boldyrev, Vladimir Alexandrovich; Nyuschenko, Ekaterina Alexandrovna; Stepanov, Michail Vladimirovich (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология)
The article presents the results of a comparative analysis of the distribution of cryptogam vascular and gymnosperms plants in the Lower Volga region based on materials from the herbarium of the Saratov State University (SARAT). Plants of the devisions Lycopodiophyta, Equisetophyta, Polypodiophyta and Pinophyta are among the ancient representatives of the fl ora of the globe. The rarity and increased vulnerability of species of these devisions is caused by both natural and anthropogenic reasons. For the entire existence of the herbarium of Saratov State University (SARAT) collected a signifi cant amount of valuable material on cryptogam vascular and gymnosperms plants, which is currently being processed and systematized. To clarify the distribution of species, the data from the report «Flora of the Lower Volga Region» and the herbarium of the SSU (SARAT) were analyzed, since when writing the fi rst volume, the herbarium data were only partially used. The herbarium of the SSU (SARAT) registered 33 species of higher spore-bearing vascular plants: Lycopodiophyta – four, Equisetophyta – six, Polypodiophyta – 19 and Pinophyta – four out of 41 species indicated in the literature for the Lower Volga region. The fund currently contains 1539 herbarium sheets related to the studied devisions the collections of which were carried out from 1902 to 2017. The most numerous is the Polypodiophyta devision, followed in descending order by the Equisetophyta, Pinophyta and Lycopodiophyta. The largest number of specimens were herbalized in the Saratov region, the Astrakhan region is in second place, and the Volgograd region is in third place. As a result of a comparative analysis for 23 species, the understanding of their distribution in the studied area has been expanded.